2010
DOI: 10.1002/pros.21314
|View full text |Cite
|
Sign up to set email alerts
|

Disparities at presentation, diagnosis, treatment, and survival in African American men, affected by prostate cancer

Abstract: Background Prostate cancer (PCa) remains the most common malignancy and the second leading cause of cancer death among men in the United States. PCa exhibits the most striking racial disparity, as African American men are at 1.4 times higher risk of being diagnosed, and two to three times higher risk of dying of PCa, compared to Caucasian men. The etiology of the disparity has not been clearly elucidated. The objective of this paper is to critically review the literature and summarize the most prominent PCa ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
260
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(275 citation statements)
references
References 90 publications
8
260
0
2
Order By: Relevance
“…Other studies have established differences in prostate cancer treatment modality between race/ethnicity groups. 9,[11][12][13]21 The current study also found differences in treatment associated with race/ ethnicity, even adjusting for other clinical and sociodemographic factors. Comparing patients residing in different population-dense counties, we found variation in treatment despite adjustment for case mix in terms of prostate cancer disease characteristics.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Other studies have established differences in prostate cancer treatment modality between race/ethnicity groups. 9,[11][12][13]21 The current study also found differences in treatment associated with race/ ethnicity, even adjusting for other clinical and sociodemographic factors. Comparing patients residing in different population-dense counties, we found variation in treatment despite adjustment for case mix in terms of prostate cancer disease characteristics.…”
Section: Discussionsupporting
confidence: 60%
“…[5][6][7] In addition, treatment decisions vary with race/ethnicity, income and marital status. [8][9][10] Few studies have examined whether treatment decisions for localized prostate cancer differ by urban, suburban or rural geographical region. Some investigators have found no difference in the proportion receiving surgery and radiation between urban and rural men, while others have found a higher likelihood of radiation in men residing in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] It is difficult to explain why Black, Hispanic, and other minority patients are less likely to receive proton therapy for prostate cancer despite these robust adjustments. One could argue patient preference plays a large role, 20 however the patients in our study all received radiation therapy and so it is highly unlikely that minority patients were overwhelmingly less likely to prefer the more resource limited proton therapy vs other forms of radiation therapy.…”
mentioning
confidence: 99%
“…A systematic review of these disparities revealed that African-American men present at a younger age and also have higher-risk disease and higher tumour volumes. 27 Similarly the management of low-risk disease in African-Caribbean men has also been scrutinised. There is increasing concern regarding the role of active surveillance in low-risk prostate cancer in African-Caribbean men.…”
Section: Management and Outcomesmentioning
confidence: 99%